The integration of quality management functions within a university: A systems approach - Brits, HJ (South African Journal of Higher Education, 2011)
According to a recent study, institutions of higher learning in South Africa fail to a great extent to integrate the key management functions that are fundamental to effective quality management. This article argues that the effective promotion of quality of a university’s core business depends to a large extent on the ability of an institution’s subsystems to function as interdependent components. The notion of integration concurs with the fundamental principles of the systems theory. This article demonstrates from a systems approach the integration of quality management, planning and resource allocation as fundamental elements in enhancing the quality of an institution’s core business.